Wireless Magnetometer for Vehicle Count and Monitoring on Thingspeak Dashboard - Ahmad Shamsudin, Asma Afifah; Ngieng Sing Yii, Bryna; Ariffin, Nainunis; Samat, Nur Alwani; Yap, Sze Ly; Soon, Chin Fhong (Evolution in Electrical and Electronic Engineering, 2021)
Manually gather statistical data on the traffic density levels is not efficient in enhancing the traffic control system. Current intrusive traffic surveillance technology was found causing large damage on the road surface and high cost. Thus, a wireless magnetometer sensor capable of implanting in the road with a small uniform area was developed to measure the three-axis magnetic flux changes when a vehicle passes over the sensor. This system consists of an HMC5883L magnetometer, microcontroller, and transceiver RF433MHz. The sensor data will be processed by the microcontroller, transmitted, and received via wireless transmission at 433MHz. Interfaces of wifi module ESP8266 and microcontroller at the receiver node allows network access and upload the received data to the cloud of Thingspeak via TCP protocol. In our project findings, 96% of counting accuracy is archived for real-time testing when the transmitter and receiver’s node distance is 1 meter and maintained above 80% when the distance is increased to 5 meters. 1 second to 1.3 seconds of real-time delays is obtained among the transmitter and receiver’s node distance from 1 to 5 meters. The magnetic field pattern based on the readings of the x, y, and z-axis was observed. The signal transmission is within a distance of 5 meters between transceivers and a latency of 15 seconds to the Cloud. The number of vehicles in real-time was successfully counted and monitored via Thingspeak’s dashboard.